Perlindungan Hukum Terhadap Guru Dari Kriminalisasi - Jumriani Nawawi (Al-Adalah: Jurnal Hukum dan Politik Islam, 2019)
This study focused on how legal protection for teachers from criminalization. This study aims to determine the problem of criminalization of teachers which is still a problem in society. This type of research is normative juridical research. The research was conducted qualitatively based on library research. The results of the study indicate that legal protection of teachers from criminalization in a positive legal perspective has been realized with the existence of several rules that can be a legal umbrella for the teaching profession in carrying out their duties and obligations as educators. Criminalization of teachers in Indonesia occurs because of differences in perceptions of parents and the school, especially teachers as educators. Penalties that provide deterrent effects such as pinching, tweaking and other disciplinary actions are considered human rights violations based on the child protection law according to the perceptions of parents. While the teacher still considers the sanctions to be included in the education category. Criminalization of teachers raises an attitude of lack of confidence in teachers in educating so that in carrying out their duties the teacher is only a teacher not as an educator.Keywords: teacher; criminalization; protection.